(untitled) (Revista Contexto & Educação, 2022)
The concept of citizenship translates into a participatory, individual, and collective process. It demands from everyone, and from those with whom it interacts, a reflection and awareness, a decision, and an action on the problems felt by itself and by society. These attributes thus seem to be able to benefit from an educational process, because citizenship is learned. This work, of an argumentative nature, aims to build a deductive-argumentative framework that defends the introduction of the theme of first aid in all education and compulsory schooling. Several structuring curriculum documents were analyzed (National Strategy for Education for Citizenship, references for education for citizenship, normative documents). It argues the creation of a first aid framework, for education for citizenship, across the spectrum of education and compulsory education, in order to contribute to a society based on the dignity of the human person, more responsible, solidary, altruistic in the commitment with the other.